Active methodologies and digital technologies during remote teaching: conceptions of public school chemistry teachers in the interior of the state of São Paulo - Leonardo Augusto da Silva; Gustavo Bizarria Gibin (Universidade Cruzeiro do Sul, Ensino de Ciências e Matemática, 2023)
During remote teaching, teachers were challenged to use methodologies and technologies that provide active and effective learning for students. This challenge results from the lack of experience and training of teachers on these subjects. This study aimed to understand the conceptions of a group of chemistry teachers from the public school system in the interior of São Paulo, regarding the use of active methodologies supported by digital technologies during the pandemic. Moran and Valente's ideas were adopted as a theoretical framework and the approach used was qualitative. Semi-structured interviews were used in data collection and for data analysis, lexical analysis was used with the Iramuteq software. It was noted that the professors did not use active methodologies and as a technological resource they mainly used simulators. The lack of structure and guidelines were some of the challenges found, which implies the need for investments in technologies and offers of teacher training on these topics.